Educating for Peace and Human Rights: An Introduction - Gerstner, Nicki; Shin, Jungyoon (In Factis Pax: Journal of Peace Education and Social Justice, 2022)
Review of Maria Hantzopoulos and Monisha Bajaj, Educating for Peace and Human Rights: An Introduction (London: Bloomsbury Academic, 2021). 188 pp., 36.95 (paperback), ISBN: 9781350129719.